Effectiveness of vehicle impoundment for high-range speeding offences in Victoria, Australia. (September 2020) - Watson, Angela; Kaye, Sherrie-Anne; Fleiter, Judy; Freeman, James
Highlights: Examined impact of vehicle impoundment on recidivism and subsequent crash rates among speeding offenders in Victoria, Australia. Drivers who had a vehicle impounded were more likely to be male, younger, and hold a probationary licence compared to drivers who did not. Lower offence rates were identified during the impoundment period compared to pre-impoundment and post-licence restoration periods. Some evidence that the impact of licence suspension was greater for those who experienced impoundment. The on-going use of vehicle impoundments may improve road safety outcomes. Abstract: Speeding behaviour has been shown to account for a large number of deaths and serious injuries on Australian roads. Vehicle impoundment is one countermeasure which has been implemented to discourage drivers from engaging in high-range speeding. Despite this countermeasure being used as a sanction in all Australian jurisdictions to combat high-range speeding offences, limited research has examined the effectiveness of vehicle impoundments in Australia. The purpose of this research was to examine the effectiveness of vehicle impoundment for high-range speeding offences on subsequent offence and crash rates. Data were collected from drivers with an eligible excessive speeding offence in Victoria, Australia between 1 July 2006 and 31 December 2014. During this time, there were 17, 440 impoundment eligible offences, 6, 883 (41.8 %) of which resulted in vehicle impoundment. The analysis revealed that drivers who had a vehicle impounded were more likely to be male, younger, hold a probationary licence, and to have a court offence. In terms of the effectiveness of vehicle impoundment, among high-range offenders, re-offence rates for those who had their vehicle impounded were statistically significantly lower for all licence periods compared with offenders who did not have their vehicle impounded. There was evidence of an effect of impoundment on reducing speeding re-offence rates during the impoundment period as well as some evidence that the impact of licence suspension was greater for those who experienced impoundment. Given that vehicle impoundment is a sanction which aims to discourage and/or incapacitate drivers from engaging in on-road risk taking behaviour, in this case high-range speeding behaviour, the longer-term positive effects of this sanction may assist with the on-going effort to reduce on-road risk taking behaviours.